2011
DOI: 10.1063/1.3549906
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polydisperse crowders on aggregation reactions: A molecular thermodynamic analysis

Abstract: Intracellular crowding in biological systems is usually mimicked in in vitro experiments by adding single crowders at high volume fractions, without taking into consideration the polydispersity of the crowders in the cellular environment. Here, we develop a molecular thermodynamic formalism to examine the effects of size-polydispersity of crowders on aggregation reaction equilibria. Although the predominantly common practice so far has been to appeal to the entropic (excluded-volume) effects in describing crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…There, the crowding induced changes in the diffusion of signalling molecules is expected to impact gene regulation and metabolism [127] and also alter active transport properties [21,33,34,128]. Other extensions of the current model include polydisperse static and dynamic crowders [129][130][131], cylindrical domains mimicking a typical bacterial shape [55,132], specific and non-specific tracer-crowder interactions [55,61], three-dimensional computer simulations, a variable tracer size, as well as deformable and non-spherical crowding particles [133,134].…”
Section: Discussionmentioning
confidence: 99%
“…There, the crowding induced changes in the diffusion of signalling molecules is expected to impact gene regulation and metabolism [127] and also alter active transport properties [21,33,34,128]. Other extensions of the current model include polydisperse static and dynamic crowders [129][130][131], cylindrical domains mimicking a typical bacterial shape [55,132], specific and non-specific tracer-crowder interactions [55,61], three-dimensional computer simulations, a variable tracer size, as well as deformable and non-spherical crowding particles [133,134].…”
Section: Discussionmentioning
confidence: 99%
“…These experiments showed that when comparing the sum of effects of each of the crowders alone with the effect of a mixture of crowding agents, the later have a synergistic effect on protein stability [49–52]. However, excluding a theoretical treatment [53], the effect of defined mixed crowding agents on association of protein complexes has not been reported. Along the same lines, cell extracts and bacterial lysates were used to achieve an improved representation of the in‐cell composition of molecules.…”
Section: In Vitro Crowding Studiesmentioning
confidence: 99%
“…It has been shown on numerous occasions that protein conformation 10,11 , folding 1215 , association 1618 , dynamics 19,20 , and aggregation 21,22 are highly affected by the excluded volume effect. These results can be interpreted as entropic effects because of the confinement 2325 and as thermodynamic effects as a result of deviations from ideal solution behavior 26,27 . Although disregarded by most in vitro studies, it has also been shown that the presence of crowding is essential for DNA transcription and replication to correlate the in vitro results to in vivo counterparts 28 .…”
Section: Introductionmentioning
confidence: 97%